2021
DOI: 10.1186/s13052-021-01114-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing gentamicin dosing in different pediatric age groups using population pharmacokinetics and Monte Carlo simulation

Abstract: Introduction The use of once daily dosing of aminoglycosides in pediatrics is increasing but studies on dose optimization targeting the pediatric population are limited. This study aimed to derive a population pharmacokinetic model of gentamicin and apply it to design optimal dosing regimens in pediatrics. Methods Population pharmacokinetics of gentamicin in pediatrics was described from a retrospective chart review of plasma gentamicin concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…Population pharmacokinetic (PPK), combined with a Monte Carlo simulation, provide feasible technical support for solving initial dosage recommendations in clinical practice. In recent years, more and more related research has been reported, which further verifies the reliability and practicability of this method (Jaruratanasirikul et al, 2019;Ren et al, 2019;Ghoneim et al, 2021;Rinaldi et al, 2021;Tang Girdwood et al, 2022). Hence, the present study recommends initial dosages of sirolimus in pediatric patients with PIK3CD mutationrelated immunodeficiency disease based on PPK and a Monte Carlo simulation.…”
Section: Introductionsupporting
confidence: 68%
“…Population pharmacokinetic (PPK), combined with a Monte Carlo simulation, provide feasible technical support for solving initial dosage recommendations in clinical practice. In recent years, more and more related research has been reported, which further verifies the reliability and practicability of this method (Jaruratanasirikul et al, 2019;Ren et al, 2019;Ghoneim et al, 2021;Rinaldi et al, 2021;Tang Girdwood et al, 2022). Hence, the present study recommends initial dosages of sirolimus in pediatric patients with PIK3CD mutationrelated immunodeficiency disease based on PPK and a Monte Carlo simulation.…”
Section: Introductionsupporting
confidence: 68%
“…Li et al reported population pharmacokinetics of polymyxin B and dosage optimization in renal transplant patients (Li et al, 2021). Ghoneim et al (2021) reported optimizing gentamicin dosing in different pediatric age groups using population pharmacokinetics and Monte Carlo simulation. Wang et al (2021) reported population pharmacokinetics of the anti-PD-1 antibody camrelizumab in patients with multiple tumor types and a model-informed dosing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that a Cmin of less than 2 mg/L decreased the risk of toxicity caused by gentamicin; thus, a gentamicin dose of 7.0 mg/kg once daily can be used to achieve a Cmin of less than 2 mg/L in the pediatric population [ 19 ]. Recently, the optimal gentamicin dosage in different pediatric age groups was investigated using population PK and Monte Carlo simulations [ 20 ]. Infants require daily doses of at least 4.0–8.0 mg/kg.…”
Section: Discussionmentioning
confidence: 99%